PENGGUNAAN STRATEGI KETIDAKSANTUNAN JULUKAN TAK PANTAS DALAM SINIAR DEDDY CORBUZIER - Anisah Hanif (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
This research focused on the varieties of the use of improper nicknames as manifestations of impoliteness in using languages. The identification was based on the linguistic markers traced from the origins of the words used as the nicknames for the speech partners. Apart fro that, the identification was also emphasized on the purpose of using nicknames in speech acts. By applying qualitative-descriptive approach, the data of ths research are five oral conversations between the host and the guest taken from the podcast hosted by Deddy Corbuzier and broadcasted on YouTube. For collecting the data, the researcher combined two techniques based on linguistic and pragmatic perspective. Menawhile, for analyzing the data, pragmatic contextual analysis was applied. The findings showed that the use of improper nicknames can be distinguished into two, namely linguistic markers and the purpose of use. Some variants found are improper names by analogy, animal names, and disgusting objects, and negative facts.